2019
DOI: 10.1007/s00203-019-01742-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenazine-1-carboxylic acid by Klebsiella sp. NP-C49 from the coral environment in Gulf of Kutch, India

Abstract: Coral-associated microbes from Marine National Park (MNP), Gulf of Kutch (GoK), Gujarat, India, were screened for siderophore production. Maximum siderophore-producing isolate NP-C49 and its compound were identified and characterized. The isolate was identified as Klebsiella sp. through 16S rRNA genes sequencing (GenBank accession nos. KY412519 and MTCC 25160). Antibiotic susceptibility profile against 20 commercial antibiotics showed its more sensitivity compared to human pathogenic strain, i.e., Klebsiella p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In agreement, we found that the relative abundance of Desulfovibrio was the highest in the mulched and high N fertilization level treatment. In addition, straw mulching combined with N fertilization led to higher relative abundances of Azotobacter, Klebsiella, and Paraburkholderia that participate in the N cycle in soil ecosystems and have plant growth-promoting properties (Li et al, 2019;Patel et al, 2019;Castellano-Hinojosa and Strauss, 2020;Liu et al, 2020;Mukherjee et al, 2020;Ravi et al, 2020), suggesting that straw return may further contribute to the growth of plants.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, we found that the relative abundance of Desulfovibrio was the highest in the mulched and high N fertilization level treatment. In addition, straw mulching combined with N fertilization led to higher relative abundances of Azotobacter, Klebsiella, and Paraburkholderia that participate in the N cycle in soil ecosystems and have plant growth-promoting properties (Li et al, 2019;Patel et al, 2019;Castellano-Hinojosa and Strauss, 2020;Liu et al, 2020;Mukherjee et al, 2020;Ravi et al, 2020), suggesting that straw return may further contribute to the growth of plants.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Paradoxically, many fungi that are sensitive to phenazines are routinely found living in close proximity to phenazine-producing bacteria, including pathogenic fungi in the lungs of cystic fibrosis patients and beneficial and phytopathogenic fungi in the rhizosphere and in oceanic environments, including coral. [9][10][11][12] This pattern of co-habitation indicates there may be a general way fungi are screened for membership in microbial communities that produce phenazines that holds broad relevance. We set out to identify such a putative screening mechanism, a necessary step toward the goal of manipulating these microbial communities for human benefit.…”
Section: Introductionmentioning
confidence: 99%
“…Given that drier soils are also associated with higher rates of phenazine producers colonizing wheat, this suggests that soil fungi may need to contend with higher concentrations of phenazines as the climate shifts 7,8 . Paradoxically, many fungi that are sensitive to phenazines are routinely found living in close proximity to phenazine-producing bacteria, including pathogenic fungi in the lungs of cystic fibrosis patients, beneficial and phytopathogenic fungi in the rhizosphere, and in oceanic environments including coral [9][10][11][12] . This pattern of co-habitation indicates there may be a general way fungi are screened for membership in microbial communities that produce phenazines that holds broad relevance.…”
Section: Introductionmentioning
confidence: 99%